Memahami Kompleksitas Manajemen Perguruan Tinggi, Sebuah Tinjauan Teori Organisasi Pendidikan Tinggi - Riswanda Priyatna (LPPM AMIK Citra Buana Indonesia, 2017)
University is one of national education sub system. University has very important function as Tri Dharma of University. There are education, research and community development like noted at UU no. 20 at 2003 about National education System. Characteristic of University in Indonesia must have: 1) student need, national priority, and economic development, 2) effective and give contribution to social and state, 3) fund support and innovation to get quality, 4) research for national development, 5) access for development and technology, 6) moral power to social democratic. So, university must have institutional credibility. The system must have accountability, efficiency and quality graduation, and standardization internal management. Key Word: management, university, complexity, higher, education